2007
DOI: 10.1128/jcm.00563-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Emerging Pathogen, Mycobacterium massiliense , by rpoB Sequencing of Clinical Isolates Collected in the United States

Abstract: Mycobacterium massiliense is a rapidly growing mycobacterium that is indistinguishable from Mycobacterium chelonae/M. abscessus by partial 16S rRNA gene sequencing. We sequenced rpoB, sodA, and hsp65 genes from isolates previously identified as being M. chelonae/M. abscessus and identified M. massiliense from isolates from two patients with invasive disease representing the first reported cases in the United States.Rapidly growing mycobacterium infections are increasing in the United States (7) and are difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 14 publications
8
68
0
1
Order By: Relevance
“…Os surtos de infecções por outras espécies de MCR são raros e publicações recentes indicam possível emergência de espécies como M. massiliense, M. mucogenicum e M. phocaicum em quadros clínicos respiratórios, de infecção local ou disseminada após procedimentos invasivos 7 .…”
Section: Epidemiologia De Infecções Por Mcr No Mundounclassified
“…Os surtos de infecções por outras espécies de MCR são raros e publicações recentes indicam possível emergência de espécies como M. massiliense, M. mucogenicum e M. phocaicum em quadros clínicos respiratórios, de infecção local ou disseminada após procedimentos invasivos 7 .…”
Section: Epidemiologia De Infecções Por Mcr No Mundounclassified
“…All the bovine kobuvirus strains detected in our study were analyzed further by direct sequencing of their PCR amplicons with the BigDye Terminator Cycle Sequencing Kit (Applied Biosystems, Foster City, CA, USA) on an automated sequencer (ABI 3100, Applied Biosystems). The nucleotide sequences of these portions were compared with those of reference strains available in the GenBank database by using BLAST (6). Phylogenetic and molecular evolutionary analyses were conducted by using MEGA version 3.1 (7).…”
Section: Bovine Kobuviruses From Cattle With Diarrheamentioning
confidence: 99%
“…Since then, Chrissoheris et al (2008) have reported successful treatment of this infection by removal of the pacemaker and 8 weeks of trimethoprimsulfamethoxazole therapy. More generally, among the few cases of pacemaker site infection due to RGM, antimicrobial therapy including one or a combination of two drugs was given for 1-6 months and was associated with the removal of the pacemaker in all cases except one involving M. fortuitum (Giannella et al, 2007;Simmon et al, 2007;Siu et al, 2005). In this latter case, the patient was given ciprofloxacin in association with clarithromycin for 6 weeks with no relapsing infection (Pastor et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…No pacemaker site infection caused by the other two species of the M. smegmatis group has been described so far. Moreover, RGM remain unusual causes of pacemaker site infection, with roughly a dozen cases reported in the literature that involve M. abscessus, M. fortuitum, M. chelonae, M. massiliense and M. goodii (Chrissoheris et al, 2008;Giannella et al, 2007;Simmon et al, 2007;Siu et al, 2005). The present case is, to our knowledge, the first documented M. goodii infection reported in Europe since a large majority of previously reported cases originated in the United States, the remaining being from Australia, Canada and Japan (Brown et al, 1999).…”
Section: Discussionmentioning
confidence: 99%